Bioactivity and Metabolites Compounds of Medicinal Plants Endophytic Fungi in Indonesia - Sukmawaty, Eka; Karim, Abdul; dwyana, Zarsawaty; Natsir, Hasnah; Karim, Harningsih; Ahmad, Ahyar (Journal of Tropical Biodiversity and Biotechnology, 2024)
Indonesia is rich in diversity of medicinal plants, vital in traditional medicine and the pharmaceutical industry. However, overharvesting, along with population growth, land use changes, deforestation, and climate change, endanger these plants. This review investigates the potential of endophytic endosymbiont as an alternative. These endosymbionts can synthesise bioactive compounds similar to those found in medicinal plants.  This study compiled data from various sources on endophytic fungi and their bioactivity. The review aims to categorise Indonesian medicinal plants, to identify their associated endophytic fungi from different plant parts, and to assess their bioactivity. The results revealed numerous medicinal plant families and a variety of endophytic fungi isolated from fruits, leaves, twigs, bark, roots, and rhizomes. These fungi exhibited bioactivities, including antioxidant, anticancer, antidiabetic, and antimicrobial effects, with metabolites such as alkaloids, flavonoids, peptides, phenols, polyketides, quinones, steroids, and terpenoids. Fusarium and Colletotrichum were the most common endophytic fungi found. Notably, the biological activity was consistent among endophytic fungi from various host organs, but variations were observed according to the host's geographical origin. This suggests that Indonesia's diverse geography influences metabolite production and activity. However, the same host plant may harbour different species in distinct organs. These findings indicate that endophytic fungi within medicinal plants represent a promising source of bioactive compounds for future Indonesian medicine production. Future research should explore metabolite compounds and bioactivity across different geographical regions.